Constructing surface-driven lithium ion storage structure for high performance hybrid capacitor. (10th March 2019) - Li, Hongxia; Chen, Jiangtao; Yang, Bingjun; Wang, Kunjie; Zhang, Xu; Zhang, Tianyun; Zhang, Li; Liu, Weisheng; Yan, Xingbin
Abstract: Because of the potential integration the high energy density of lithium ion batteries and high power output of electrochemical capacitors, lithium ions hybrid capacitors (LIHCs) have been emerged as one of the promising electrochemical energy storage devices. Developing suitable battery-type anodes and capacitive-type cathodes are important to achieve high-performance LIHCs. Herein, we construct an orthorhombic niobium pentoxide/carbon ( T -Nb2 O5 /C) nanocomposite with surface-driven lithium ion storage merit via a facile pyrolysis of Nb-based coordination-polymer. The synthesized T -Nb2 O5 /C exhibits higher capacity and a much better rate capability compared to commercial Nb2 O5 . At the same time, benefiting from the host-guest chemistry, we synthesize a high-capacitance N-doped porous carbon cathode through annealing the mixture of β -cyclodextrin and urea combined with a potassium hydroxide activation. As a consequence, an advanced LIHCs is built based on the above electrode materials, that delivers a high energy density (92 W h kg − 1 ) and high power density (17.5 kW kg − 1 ) within the wide potential window of 0–3.5 V. A superior cycling performance is also delivered by our device with 86% of the capacitance retention after 10 000 cycles at the 2 A g − 1, successfully bridging the performance gap between conventional batteries and supercapacitors.